Upaya Meningkatkan Kemampuan Berbicara Bahasa Arab Siswa dengan Menggunakan Metode Audiolingual - Munir, Dede Rizal; Julianti, Julianti; Maftuhah, Maftuhah (Tadris Al-'Arabiyyah: Jurnal Pendidikan Bahasa Arab dan Kebahasaaraban, 2023)
This research is motivated by students who still have difficulty learning to speak, especially when using the dialogue model. The aim of this research is to find out how the application of the audiolingual approach in Arabic language learning improves the speaking skills of 38 class IX students at Ibnu Sina Middle School, Purwakarta. This research was carried out from May to June 2023, the type of research was Classroom Action Research (PTK) which was carried out cyclically. The research data sources are teacher and student observations and evaluation of student abilities. Data collection techniques are observation and evaluation. Data analysis techniques determine individual completion, classical completion, and average scores. The results show that the audiolingual approach can improve student learning achievement in Arabic speaking skills. Growing student involvement in the learning process shows the effectiveness of the method, and the growing importance of learning outcomes reveals that the students' speaking skills in Cycle I was 77.96 (Fairly Good) and Cycle II was 80.59 (good), indicating the effectiveness of the results. Engagement rates ranged from 83.8% (good) in Cycle 1 to 89.1% (excellent) in Cycle 2.